A review of the linyphiid spider genus Proislandiana Tanasevitch, 1985 with description of a new high mountainous species from Turkey and Armenia (Araneae: Linyphiidae) - Dimitrov, Dragomir (Zootaxa, 2020)
A new species of the hitherto monotypic spider genus Proislandiana Tanasevitch, 1985 is described from the high altitude belt of Ararat Mountain (Turkey) and Aragats Mountain (Armenia). The genus Proislandiana is reviewed, its taxonomic relationships to the other genera are discussed. The diagnoses of the genus and its type species are revised. The distribution and the zoogeography of the two known Proislandiana species are summarized and discussed.